2014
DOI: 10.1098/rsif.2013.1029
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of crystal orientations of the multi-domain photonic crystals in Parides sesostris wing scales

Abstract: It is known that the wing scales of the emerald-patched cattleheart butterfly, Parides sesostris, contain gyroid-type photonic crystals, which produce a green structural colour. However, the photonic crystal is not a single crystal that spreads over the entire scale, but it is separated into many small domains with different crystal orientations. As a photonic crystal generally has band gaps at different frequencies depending on the direction of light propagation, it seems mysterious that the scale is observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 41 publications
1
41
1
Order By: Relevance
“…The polycrystalline arrangement of the single-gyroid chitin structure shows a preferred alignment of certain crystallographic directions w.r.t the scale's outer surface normal, named crystallographic texture. Our findings of 12.5% and 32.5% of crystallites oriented along the <111> and <100> crystallographic directions, respectively, are in stark contrast to the observation in another gyroidforming butterfly, P. sesostris, where a strong prevalence of the <110> direction is observed (9). This difference in the degree of crystallographic texture between these two species is in accordance with the optical appearance of the wing scales, which show a rather uniform color in the case of P. sesostris and spatial variations of reflectivity for C. rubi.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The polycrystalline arrangement of the single-gyroid chitin structure shows a preferred alignment of certain crystallographic directions w.r.t the scale's outer surface normal, named crystallographic texture. Our findings of 12.5% and 32.5% of crystallites oriented along the <111> and <100> crystallographic directions, respectively, are in stark contrast to the observation in another gyroidforming butterfly, P. sesostris, where a strong prevalence of the <110> direction is observed (9). This difference in the degree of crystallographic texture between these two species is in accordance with the optical appearance of the wing scales, which show a rather uniform color in the case of P. sesostris and spatial variations of reflectivity for C. rubi.…”
Section: Discussioncontrasting
confidence: 55%
“…It is an essential determinant of color uniformity, because the photonic properties of the single gyroid strongly depend on the crystal orientation (12,23). Yoshioka et al (9) observed a highly textured crystal orientation within scales of the butterfly Parides sesostris. Although the scales of P. sesostris exhibit a multicrystalline structure on the micrometer scale, they appear to be rather uniform in color, which is linked to the preferential orientation of the nonchiral <110> direction of the individual crystallites parallel to the surface normal of the scales.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In insects, these are found in wing scales of nearly all families of butterflies, weevils, and beetles and are composed of cuticle sculpted into 3D minimal surfaces ( Figure 13D-F). [314][315][316][317][318][319][320] Light-matter interaction in these photonic crystals becomes highly dependent on the orientation of the photonic crystal, as well as the direction of incident light. Due to the low refractive-index contrast of cuticle and air (≈1.55), these photonic crystals cannot build a full photonic bandgap, but show a pronounced iridescence due to partial optical bandgaps that can be well explained by photonic bandgap modeling.…”
Section: Structural Colorationmentioning
confidence: 99%
“…Each different morphology changes the way light interacts with the structure, as do local defects and disorder. Insect nanomorphologies range from ordered structures starting from thin films [309][310][311] and multilayer structures [277,282,304,312,313] to 3D photonic crystals to quasi-ordered and fully disordered structures, [314][315][316][317][318][319][320] each with different optical properties.…”
Section: Structural Colorationmentioning
confidence: 99%